Atlas of environmental issues - Middleton, Nick; Weston, Steve; Downes, John (New York : Facts on File, 1989)
Describes and explains major environmental issues of the world today including soil erosion, deforestation, mechanised agriculture, oil pollution of the oceans, acid rain, overfishing, and nuclear power.
Includes index
Keywords: Nature conservation -- Juvenile literature; Pollution -- Environmental aspects -- Juvenile literature; Nature -- Effect of human beings on -- Juvenile literature; Environmental protection -- Juvenile literature; Conservation of natural resources; Pollution -- Environmental aspects; Nature -- Effect of human beings on; Environmental protection